Description of a new species of Hoolock gibbon (Primates: Hylobatidae) based on integrative taxonomy. Issue 5 (10th January 2017) - Fan, Peng‐Fei; He, Kai; Chen, Xing; Ortiz, Alejandra; Zhang, Bin; Zhao, Chao; Li, Yun‐Qiao; Zhang, Hai‐Bo; Kimock, Clare; Wang, Wen‐Zhi; Groves, Colin; Turvey, Samuel T.; et al.
Abstract : We describe a species of Hoolock gibbon (Primates: Hylobatidae) that is new to science from eastern Myanmar and southwestern China. The genus of hoolock gibbons comprises two previously described living species, the western ( Hoolock hoolock ) and eastern hoolock ( H. leuconedys ) gibbons, geographically isolated by the Chindwin River. We assessed the morphological and genetic characteristics of wild animals and museum specimens, and conducted multi‐disciplinary analyses using mitochondrial genomic sequences, external morphology, and craniodental characters to evaluate the taxonomic status of the hoolock population in China. The results suggest that hoolocks distributed to the east of the Irrawaddy‐Nmai Hka Rivers, which were previously assigned to H. leuconedys, are morphologically and genetically distinct from those to the west of the river, and should be recognized as a new species, the Gaoligong hoolock gibbon or skywalker hoolock gibbon ( H. tianxing sp. nov.). We consider that the new species should be categorized as Endangered under IUCN criteria. The discovery of the new species focuses attention on the need for improved conservation of small apes, many of which are in danger of extinction in southern China and Southeast Asia. Abstract : Based on morphological and genetic characteristics, we describe a new species of hoolock gibbon ( Hoolock tianxing ) that is distributed between the Irrawaddy‐Nmai Hka Rivers and the Salween River, which is previously assigned to H. leuconedys .